2000
DOI: 10.1002/(sici)1097-4628(20000523)76:8<1338::aid-app15>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Quinone-amine polyurethanes: new coupling agents for the steel-epoxy system

Abstract: ABSTRACT:A new series of quinone-amine polyurethanes (QAPs) were synthesized using toluene diisocyanate, polytetrahydrofuran, and an amine-quinone monomer (AQM1). The AQM1 was synthesized and characterized using spectroscopic techniques (UV, IR, NMR). The QAP synthesis involved a two-step process and yielded block copolymers. These polymers were characterized using infrared spectroscopy, thermal analysis methods (thermogravimetric analysis and differential scanning calorimetry) and gel permeation chromatograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…This result can be attributed to the addition of hydrophobic BB into the epoxy resins which increases the adhesion of the aluminum–epoxy systems through chemical interaction, mediated by the quinone molecule free electrons to the outer orbital of the metal surface through chemisorption 9–11, 20. A similar observation was made with quinone‐amine polyurethanes obtained from toluene diisocyanate, polytetrahydrofuran, and amine‐quinone monomer 21…”
Section: Resultsmentioning
confidence: 54%
“…This result can be attributed to the addition of hydrophobic BB into the epoxy resins which increases the adhesion of the aluminum–epoxy systems through chemical interaction, mediated by the quinone molecule free electrons to the outer orbital of the metal surface through chemisorption 9–11, 20. A similar observation was made with quinone‐amine polyurethanes obtained from toluene diisocyanate, polytetrahydrofuran, and amine‐quinone monomer 21…”
Section: Resultsmentioning
confidence: 54%
“…These polyurethanes were shown to inhibit the corrosion of the commercial iron particles used in state‐of‐the‐art metal particle tape 10–13. We also demonstrated that amine–quinone polyurethanes promote the adhesion of epoxy to steel 14, 15…”
Section: Introductionmentioning
confidence: 62%
“…The amine–quinone polyurethanes and the amine–quinone polyimides provide an opportunity to test this model. We have already shown that amine–quinone polyurethanes promote adhesion of epoxy to steel 14, 15. We speculate that the amine–quinone polymers chemisorb to the iron surface and expect that the bond strength would depend on the nature of the amine–quinone functional group and the number of groups adsorbing to the iron surface.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations